2013
DOI: 10.1080/13573322.2013.837044
|View full text |Cite
|
Sign up to set email alerts
|

The position of dance in physical education

Abstract: Dance has been a part of the physical education (PE) curriculum in several countries for a long time. In spite of this, studies demonstrate that the position of dance in the subject of PE is contested and that little time is devoted to dance. The overall aim of this article is to examine the position of dance as a pedagogical discourse in Swedish steering documents over time. The empirical material consists of five Swedish curricula for PE over a period of 50 years . Discourse analysis is used to identify orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 37 publications
0
31
2
3
Order By: Relevance
“…In addition, 62% (N = 53) of schools offered dance in an extra curricular programme either during lunch times or in an after-school club. To identify the types of experiences that pupils were experiencing in dance was important, as Mattsson and Lundvall (2015) identify that dance can serve different functions and transmit associated knowledge. The results from the questionnaire indicated that the styles of dance experienced by pupils were wide and varied, including Hip hop, Street, Jump, Bollywood, Scottish Country dance, Jazz, Interpretive, Ethnic, Contemporary, Breakdance, Ballroom, Ballet and Tap.…”
Section: Curricular Dance Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 62% (N = 53) of schools offered dance in an extra curricular programme either during lunch times or in an after-school club. To identify the types of experiences that pupils were experiencing in dance was important, as Mattsson and Lundvall (2015) identify that dance can serve different functions and transmit associated knowledge. The results from the questionnaire indicated that the styles of dance experienced by pupils were wide and varied, including Hip hop, Street, Jump, Bollywood, Scottish Country dance, Jazz, Interpretive, Ethnic, Contemporary, Breakdance, Ballroom, Ballet and Tap.…”
Section: Curricular Dance Opportunitiesmentioning
confidence: 99%
“…To provide a background for the current study, the paper will initially consider the significance of teacher agency within the contextual dimensions of the school as an important factor in enabling teachers to include dance in the curriculum. Subsequently, a variety of dance styles and their educational value will be considered by using Mattsson and Lundvall's (2015) pedagogical discourses as a framework for analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Begrunnelsen for dette skillet fremgår ikke i planverket, men i et kjønnsperspektiv sier det mye om oppfatning av dans og speiler kjønnsdimensjonen ved dans i kroppsøving som et vedvarende tema. Kjønnsdimensjonen kommer i dag til syne både ved at flere jenter enn gutter ønsker mer dans, og at kvinnelige kroppsøving-slaerere bruker mer tid på dans enn mannlige (Nordaker, 2009;Mattsson & Lundvall, 2015).…”
Section: Dans I Kroppsøvingsfaget Fra 1939unclassified
“…Selv om kartleggingen etter L97 antydet at dans var i ferd med å styrke sin posisjon som del av praksisen i kroppsøvingsfaget, og at undersøkelsen viser variasjon i inkludering av og kompetanse i dans, virker dans generelt fortsatt å stå svakt blant kroppsøvingslaerere i Norge (Jacobsen, 2003;Jacobsen et.al., 2006). Norge virker på dette punkt ikke å skille seg vesentlig fra utfordringer med dans i kroppsøving internasjonalt (Sanderson, 1996;Mattsson & Lundvall, 2015). I det følgende vil vi gjennomgå laereplanen som utgangspunkt for å se naermere på Nordakers (2009) ytring om at den representerer et tilbakeskritt for de gode intensjonene med dans i kroppsøving.…”
Section: Dans I Kroppsøvingsfaget Fra 1939unclassified